Micropropagation of a Medicinal Plant (Azlma tetracantha Lam.) - Benniamin, A.; Sundari, M. S. (Indian Forester, 2011)
Tissue cultures system was established from shoot tips of the A. tetracantha. Shoot proliferation was achieved with MS medium supplemented with different concentrations of Kinetin. Stocking of shoot cultures was obtained by repeating subculture in the same medium at 40 day intervals where in the rate of multiplication was maintained. For rooting, the individual shoots were implanted on root induction medium consisted of MS medium supplemented with O.4mg/l NAA. Within two weeks of incubation 70% rooting was evidenced. The in vitro plantlets were successfully weaned and transferred to soil with 67.5% survival rate. Complete plantlets were acclimatized and succeSsfully transplanted to natural habitants.